The Tax Advantage of Big Business: How the Structure of Corporate Taxation Fuels Concentration and Inequality - Sandy Brian Hager; Joseph Baines (Politics & Society, 2020)
Corporate concentration in the United States has been on the rise in recent years, sparking a heated debate about its causes, consequences, and potential remedies. This article examines a facet of public policy that has been neglected in the debate: corporate taxation. Developing the first empirical mapping of the effective tax rates of nonfinancial corporations disaggregated by size and broken down by jurisdiction, the article reveals a striking tax advantage for big business at home and abroad. The analysis goes on to show how persistent regressivity in the tax structure is bound up with the increasing relative power of large corporations within the corporate universe, as well as a shift in firm-level power relations. As large corporations become less disposed to investments that may indirectly benefit ordinary workers, they become more disposed to shareholder value enhancement that directly benefits the asset-rich. What this means is that the corporate tax structure is connected not only to rising corporate concentration but also to widening household inequality.
Keywords: P16; H2; G3; G; 330; corporate taxation; concentration; inequality; capital as power; financialization